Penyuluhan Penggunaan Oralit Untuk Menanggulangi Diare Di Masyarakat - Harianto, Harianto (Majalah Ilmu Kefarmasian, 2004)
Diarrhea is one of the common deseases and a attack any level of ages. Diarrhea can be tuated effectively by using oralit to replace the lost of body water. To increase the use of oralit against diarrhea, this trestment should be socialized to public with undergo a general lecture to enhanced the public knowledges cncerning diarrhea and causing factors, to make a group discussion of senior citizen and public figures to build positive attitude in using oralit, and to demonstrate the processing of oralit/LGG and how to use it to people.